2020
DOI: 10.3390/diagnostics10060422
|View full text |Cite
|
Sign up to set email alerts
|

Upstroke Time as a Novel Predictor of Mortality in Patients with Chronic Kidney Disease

Abstract: Upstroke time (UT), measured from the foot-to-peak peripheral pulse wave, is a merged parameter used to assess arterial stiffness and target vascular injuries. In this study, we aimed to investigate UT for the prediction of cardiovascular and all-cause mortality in patients with chronic kidney disease (CKD). This longitudinal study enrolled 472 patients with CKD. Blood pressure, brachial pulse wave velocity (baPWV), and UT were automatically measured by a Colin VP-1000 instrument. During a median follow-up of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…23 out of the 48 included studies reported a higher cardiovascular mortality rate in men than women, with risk estimates ranging from 1.16 to 3.51 (Tables 2 and 3 ) [ 18 20 , 25 , 30 , 35 , 37 , 38 , 42 , 45 , 55 , 57 , 58 , 60 62 ]. However, 18 of the 48 studies showed that men had a lower risk of cardiovascular mortality compared to women, with risk estimates ranging from 0.29 to 0.93 (Tables 2 and 3 ) [ 23 , 24 , 34 , 39 , 44 , 46 , 47 , 49 , 53 , 54 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 out of the 48 included studies reported a higher cardiovascular mortality rate in men than women, with risk estimates ranging from 1.16 to 3.51 (Tables 2 and 3 ) [ 18 20 , 25 , 30 , 35 , 37 , 38 , 42 , 45 , 55 , 57 , 58 , 60 62 ]. However, 18 of the 48 studies showed that men had a lower risk of cardiovascular mortality compared to women, with risk estimates ranging from 0.29 to 0.93 (Tables 2 and 3 ) [ 23 , 24 , 34 , 39 , 44 , 46 , 47 , 49 , 53 , 54 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the studies reported results for end-stage renal disease (ESRD) patients on dialysis: 30 studies included subjects exclusively on HD [15,16,19,20,, eight studies included subjects on PD [48][49][50][51][52][53][54][55], three studies included both HD and PD [17,18,56], and six studies reported their subjects were not on dialysis [21,[57][58][59][60][61]. Six studies defined their subjects as having CKD stages 3 to 5, [18,21,58,59,61,62], while only one study described their subjects as CKD stages 3 and 4 [60]. In addition to this, most studies (33/48) reported comorbidity with diabetes mellitus and hypertension.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The phenomenon of the prolonged UTCC with normal ABI is based on various collateral arterial networks with severe PAD, including chronic total occlusion of peripheral arteries. Based on this background, UTCC has been reported to be a significant parameter for mortality prediction in diseased patients such as type 2 diabetes mellitus 4) , chronic kidney disease 5) , or acute myocardial infarction 6) .…”
Section: See Article Vol 28: 000-000mentioning
confidence: 99%